Pengaruh Aditif Sodium Lauryl Sulfate dan Carboxy Methyl Cellulose pada Pembuatan Coal Water Mixture - I Gusti S. Budiaman; S. Diyar Kholisoh; Placidia Osita O.; Priscilla Hilary K. (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Nowadays Indonesia’s energy needs are increasingly high and estimated at about 2 million barrels of oilequivalent (2 MMBOE). Indonesia's oil reserves are already dwindling, while coal has not well-utilized yet.Recent utilization of coal in the solid phase causes incomplete combustion. An alternative way to completethe combustion is by converting coal into CWM (coal water mixture). CWM is expected to have similarproperties to fuel oil so that it will be more easily atomized and burned. A relatively high calorific value coalfrom Murung Raya (Central Kalimantan) was applied. CWM was experimentally prepared by crushing coalinto very fine granules, it was therefore mixed into the water added by sodium lauryl sulfate (SLS) andcarboxy methyl cellulose (CMC) as dispersant and stabilizer, respectively. Two experimental paramaterschosen in this study included parameter-1 (0,7% SLS and 0,1% CMC) and parameter-2 (0,8% SLS and 0,2%CMC), based on the total mass. Each parameter was mixed into the flask (mixing vessel) containing water.Therefore coal was gradually added with the coal-water ratio of 50%, 55%, 60%, 65%, and 70%. The mixingwas conducted for 120 minutes at temperature of about 50 °C and stirring speed of 500 rpm. The best resultof CWM was performed on parameter-2 with 55% of coal. It had a calorific value of 3845 cal/g and wasstable during its storage within 20 hours.